An Evaluation Study of The Environmental Awareness of Climate Change Among Female Players of Some Universities in The Middle Euphrates Region - Aldulimey, Nahidah Abd Zaid; Hussein, Ali Radhi Abdul (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The aim of the research is to prepare environmental awareness of climate changes among female players, as well as identifying environmental awareness of climate changes among female players in some universities in the Middle Euphrates region, as well as finding differences in environmental awareness of climate changes among female players between some group and individual games, and the researcher followed the descriptive approach in its survey and comparison styles due to its suitability with the nature of the research objectives, the research was conducted on female players in some universities in the Middle Euphrates region. As the total number of the research community reached (103) players, and the research sample of (28) players was randomly selected, the researcher prepared a measure of environmental awareness of climate change and it was presented to a group of experts and specialists, and full statistical treatments were conducted for the preparation process, using appropriate statistical methods In the light of the results obtained, the researcher reached several conclusions, the most important of which was the enjoyment of team and individual game players in some universities in the Middle Euphrates region with a good degree of environmental awareness of climate change. In addition, there is no preference in environmental awareness of climate change among team and individual game players in some universities in the Middle Euphrates region. In light of these conclusions, the researcher recommended several recommendations, including the need to pay attention to the environmental aspect of climate changes surrounding female players in general and the training environment in particular, with an emphasis on the need for great interest in clarifying and spreading environmental awareness of climate changes in various activities and different sports.